The persistence of students' academic effort: The unique and combined effects of conscientiousness and individual interest. (August 2022) - Rieger, Sven; Göllner, Richard; Spengler, Marion; Trautwein, Ulrich; Nagengast, Benjamin; Roberts, Brent W.
Abstract: The present study was designed to test the CONscientiousness × Interest Compensation (CONIC) model in a longitudinal setting (four time points; N = 3, 880 students). For this purpose, we first examined the power of conscientiousness (measured with student and parent reports) and interest in predicting perceived academic effort in three school subjects (Math, German, and English). In a second step, we investigated whether conscientiousness and interest interacted in a compensatory pattern as predicted by the CONIC model. Results showed that conscientiousness and interest significantly and positively predicted future perceived academic effort. In addition, conscientiousness and interest interacted in a compensatory manner, such that interest was less important for perceived academic effort in students who were high in conscientiousness (and vice versa). Highlights: First longitudinal test of the CONscientiousness × Interest Compensation (CONIC) model. Conscientiousness and interest prospectively predicted academic effort in math, German, and English. Compensatory mechanism empirically supported for 5 out of 9 tested interaction effects.